Felony Forfeiture at the Manor of Worfield, C.1370–C.1600. Issue 3 (2nd September 2018) - Gibbs, Spike
ABSTRACT: Felony forfeiture has recently received attention by historians working in both politico-legal and economic traditions. However, its history within the context of local lordships remains underexplored. By utilizing an exceptionally rich set of cases recorded in the court rolls of the manor of Worfield for the period c. 1370– c. 1600, this article explores the exercise of the franchisal rights to felons' goods of one manorial lord. It demonstrates that these rights were extensive, and their application provides an excellent opportunity for historians to reconstruct the material living standards of late medieval villagers. It argues that the legal context of the manorial court makes the lists of goods recorded exceptionally valuable, in that the lives of the felons who owned these goods can be explored, highlighting this through one detailed case study. The conclusion also emphasizes the importance of considering the collaboration of tenants in the manorial forfeiture process, and that this was probably a crucial element in the success of seigniorial enforcement of this franchise.